1989
DOI: 10.1210/jcem-69-6-1268
|View full text |Cite
|
Sign up to set email alerts
|

Hashimoto’s Thyroiditis and HLA in Japanese*

Abstract: To investigate genetic factors involved in the pathogenesis of Hashimoto's thyroiditis (HT; goitrous autoimmune thyroiditis), HLA class I and class II antigens were analyzed in both seropositive HT (99 patients) and seronegative HT (43 patients). The frequency of HLA-DRw53 antigen was increased significantly in both seropositive HT (antigen frequency, 0.83; relative risk, 33.3; P less than 0.0002; corrected P less than 0.001) and seronegative HT (antigen frequency, 0.81; relative risk, 3.02; P less than 0.01; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 27 publications
0
20
1
1
Order By: Relevance
“…20,21 However, the present study showed no significant association between any HLA antigens and the hypothyroid state of autoimmune pancreatitis, which suggests that the occurrence of hypothyroid state is directly correlated with autoimmune pancreatitis and not with an additional genetic background linked to the occurrence of Hashimoto's thyroiditis. In addition, AIP patients with hypothyroidism showed features atypical of Hashimoto's thyroiditis-i.e., they were preponderantly elderly males, they had no goiter, and they showed a lower prevalence of anti-TPO antibody than anti-thyroglobulin antibody.…”
Section: Hla Analysis In Patients With Autoimmune Pancreatitis (Aip) contrasting
confidence: 68%
See 1 more Smart Citation
“…20,21 However, the present study showed no significant association between any HLA antigens and the hypothyroid state of autoimmune pancreatitis, which suggests that the occurrence of hypothyroid state is directly correlated with autoimmune pancreatitis and not with an additional genetic background linked to the occurrence of Hashimoto's thyroiditis. In addition, AIP patients with hypothyroidism showed features atypical of Hashimoto's thyroiditis-i.e., they were preponderantly elderly males, they had no goiter, and they showed a lower prevalence of anti-TPO antibody than anti-thyroglobulin antibody.…”
Section: Hla Analysis In Patients With Autoimmune Pancreatitis (Aip) contrasting
confidence: 68%
“…We could find no HLA class I or II antigens for which the levels were significantly greater in hypothyroid AIP subjects than in euthyroid AIP or normal subjects, including A2, DR11, DR15, and DR53, which have been reported to be closely associated with Hashimoto's thyroiditis both in Japan and Western countries (Table 3). 20,21 Discussion Positivity for anti-Tg antibody was significantly more frequent in patients with autoimmune pancreatitis than in those with ordinary chronic pancreatitis, but there was no significant difference in the frequency of anti-TPO antibody between the two groups. It has been reported that the prevalence of autoantibodies for thyroid antigens is as high as 30% in patients with other autoimmune diseases, such as Sjoegren's syndrome 22 and systemic lupus erythematosis.…”
Section: Hla Analysis In Patients With Autoimmune Pancreatitis (Aip) mentioning
confidence: 89%
“…Data on HLA haplotypes and their association with HT have been less definitive than those on GD (Vaidya et al 2002). In addition, there are no consistency between the different studies reported on HLA association with HT, such as HLA-DQw7 in English Caucasians (Tandon et al 1991), HLA-DRB1*0405 in Greek population (Kokaraki et al 2009), HLA-DRw53 in Japanese (Honda et al 1989), and HLA-DR9 in Chinese (Hawkins et al 1987). In our study, when the frequencies of HLA DQB1-DQA1 were compared between patients and controls, positive association was found with the haplotypes DQB1*0302-DQA1*0501 (P 00.008, OR 02.378, CI 0 1.241-4.558) and DQB1*0302-DQA1*0301 (P 00.002,OR02.402,.…”
Section: Discussionmentioning
confidence: 99%
“…Associations between some HLA antigens and autoimmune thyroid diseases have consistently been observed [5,16,[18][19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Those associated with Hashimoto's disease include A2, DR2, DR3, DQ7, DRB4*0101, DQA 1 *0102 and DQB 1 *0602 [16,21]. In Japanese patients with high TSBAb activity the HLA antigens include B35, B67, Bw60 and Dw 8 [16,17].…”
Section: Discussionmentioning
confidence: 99%